Infrastructure Strategies for Achieving the Global Development Agendas in Small Islands. Issue 2 (23rd February 2021) - Adshead, Daniel; Roman, Orlando; Thacker, Scott; Hall, Jim W.
Abstract: Small island developing states face particular challenges to ensure their infrastructure promotes social, economic, and environmental well‐being. Closing the achievement gap for the Sustainable Development Goals (SDGs) involves prioritization and coordination across multiple sectors. With an application to the country of Saint Lucia, this paper develops a stakeholder‐driven analysis framework integrating four interdependent infrastructure sectors (electricity, water, wastewater, and solid waste). Drawing on extensive consultation with decision‐makers in‐country—134 stakeholders from 18 government ministries, agencies, academia, or the private sector—the analysis identifies specific interventions that could be implemented over the next decades to meet future needs for sustainable infrastructure services. These interventions are congruent with the government's development plans. Long‐term, cross‐sectoral portfolios of investments and policies ("strategies") are developed which demonstrably reach the targets of the SDGs and Saint Lucia's emissions reduction commitments under the Paris Agreement. The sequencing of these investments or policies is designed to optimize their efficiency and impact over time, identifying "quick wins" while ensuring that there is sufficient action to provide services in the long‐term sustainably. A comparison of costs associated with each strategy suggests that accounting for interdependencies and taking a long‐term perspective can save costs over the life of infrastructure investments. This process of infrastructure assessment is applicable beyond the small island context, allowing practitioners a means to undertake systematic assessment of a country's future infrastructure needs and to develop appropriate solutions aligned with its national objectives and international commitments. Plain Language Summary: Infrastructure is crucially important to achieving many development outcomes, including social (e.g., poverty, health, and education), economic, and environmental targets. Providing infrastructure services such as energy, water, and waste management has often been undertaken without accounting for the linkages between these sectors. Given that demand for these services is projected to grow around the world, this article recognizes that meeting countries' future needs in the most efficient and cost‐effective way will require infrastructure to be planned as a system. Here, we design a consistent method for doing so and demonstrate how the unique challenges of a country can be assessed and incorporated into the infrastructure planning process. Importantly, this process ensures that countries are able to align their planning as closely as possible with major international agreements such as the Sustainable Development Goals and the Paris Agreement on Climate Change. Key Points: A systematic infrastructure sustainability assessment and planning process is developed at the national level for small islands Interdependent sector planning is designed to meet challenges faced by SIDS in the energy, water, wastewater, and solid waste sectors Infrastructure strategies that are aligned with SDG and Paris Agreement targets are more cost effective in the long term